Dietary and physical activity patterns related to cardio-metabolic health among Malaysian adolescents: a systematic review - Shooka Mohammadi; Muhammad Yazid Jalaludin; Tin Tin Su; Maznah Dahlui; Mohd Nahar Azmi Mohamed; Hazreen Abdul Majid (BMC, 2019)
Abstract Background A sedentary lifestyle and an unhealthy diet are major factors in the increasing prevalence of obesity among Malaysian adolescents. The purpose of this systematic review is to compile the evidence from observational and intervention studies among Malaysian adolescents to evaluate the associations between diet and physical activity (PA) as determinants of cardio-metabolic risk factors. Methods A systematic search of Medline via the PubMed, Science Direct, Cochrane Review and Web of Science databases was conducted for studies on the associations between diet and PA factors and cardio-metabolic risk factors among Malaysian adolescents aged 13-18 years that were published until 31 August 2017. The search results were independently screened and extracted by two reviewers. Results From over 2,410 references retrieved, 20 full texts articles were screened as potentially relevant. Seventeen (16 cross-sectional and one intervention) met the inclusion criteria for data extraction and analysis. All 17 studies were rated as poor quality and the majority had made insufficient adjustment for confounders. As regards the effect of diet and PA on cardio-metabolic health, the intakes of energy (n = 4) and macronutrients (n = 3) and meal frequency (n = 5) were the most commonly studied dietary factors, while the PA score and level were the most commonly studied PA factors. In addition, BMI and body weight were the most common cardio-metabolic health outcomes. The studies showed that obese and overweight adolescents consume significantly more energy and macronutrients. They are also more likely to skip their daily meals compared to their normal weight peers. In most studies, the direction of the PA effect on body weight was unclear. Some studies found that higher PA is associated with a lower risk of overweight and obesity. However, the associations are often small or inconsistent, with few studies controlling for confounding factors. Conclusions This review identified a lack of evidence and well-conducted prospective studies on the effect of diet and PA on cardio-metabolic health of Malaysian adolescents.